Indoor air quality at school and students' performance: Recommendations of the UNESCO Chair on Health Education and Sustainable Development & the Italian Society of Environmental Medicine (SIMA) - Manuela Pulimeno; Prisco Piscitelli; Salvatore Colazzo; Annamaria Colao; Alessandro Miani (Tabriz University of Medical Sciences, 2020)
The issue of indoor air quality (IAQ) concerns 64 million students across Europe, but it is still a neglected topic, although it impacts both their health and learning outcomes. Classroommicroclimate is the first key factor determining a healthy or unhealthy school environment, and it is influenced by ventilation, temperature and humidity rate. Classrooms are usually crowded, overheated and poorly ventilated, thus resulting in possible increases of carbon dioxide (CO2), that can cause several problems when its concentrations exceed the value of 0.15 percentage volume of CO2 (1500 ppm) or even at lower levels (1000 ppm). CO2 can also arise from outside the school, being widely produced by the combustion of fossils or road traffic. Anthropogenic activities are responsible for the emission of nitrogen dioxide (NO2) and polycyclic aromatic hydrocarbons(PAH) too, which represent other possible external contaminants potentially impairing IAQ. Furtherdangerous exposures for students' health are those related to natural emission of gas Radon, which typically accumulates in poorly ventilated classrooms, and volatile organic compounds (VOCs, released by building materials, paints, furnishings, detergents), while chemicals substances (i.e.cyanoacrylate, lead, cadmium, nickel) might be contained in school materials. Finally, particulate matter (PM2.5 and PM10) originating from road traffic, domestic heating or industrial activities represent additional possible contaminants impacting schools' air quality. Poor IAQ might result in mild adverse events (i.e. headaches, nausea etc.) or cause respiratory problems. More frequently, IAQ affects students' attention and their school performances, as widely documented by many studies. Standardized tests administered to pupils exposed to poor IAQ (to assess reading and mathematical abilities) systematically result in worse outcomes compared to students staying in healthy classroom environments. In this paper, we present recommendations of UNESCO Chair on Health Education and Sustainable Development and Italian Society of Environmental Medicine(SIMA) to ensure an optimal IAQ at school, including some post-COVID-19 issues.